2020
DOI: 10.1111/jpi.12690
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects mouse testes from palmitic acid‐induced lipotoxicity by attenuating oxidative stress and DNA damage in a SIRT1‐dependent manner

Abstract: Palmitic acid (PA), the main component of dietary saturated fat, has been known to increase in patients with obesity, and PA-induced lipotoxicity may contribute to obesity-related male infertility. Melatonin has beneficial effects on reproductive processes; however, the effect and the underlying molecular mechanism of melatonin's involvement in PA-induced cytotoxicity in the testes are poorly understood. Our findings showed that lipotoxicity was observed in mouse testes after long-term PA treatment and that me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(93 citation statements)
references
References 66 publications
5
88
0
Order By: Relevance
“…Similarly, previous study con rmed that isorhamnetin inhibited collagen deposition in N2a cells by alleviating ERS [26]. ERS could disturb the balance of Ca2+ [27]. Research have shown that isorhamnetin inhibited Ca2+ overload and alleviated ERS-induced apoptosis in N2a cells [26].…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, previous study con rmed that isorhamnetin inhibited collagen deposition in N2a cells by alleviating ERS [26]. ERS could disturb the balance of Ca2+ [27]. Research have shown that isorhamnetin inhibited Ca2+ overload and alleviated ERS-induced apoptosis in N2a cells [26].…”
Section: Discussionsupporting
confidence: 53%
“…To determine the involvement of ER stress in wogonoside-induced apoptosis of the AGS and MKN-45 cell lines, the activation of the ER stress pathway was determined. Compared with that in the control group the exposure to wogonoside significantly increased the protein and mRNA expression levels of CHOP, a known ER stress-related marker ( 21 ), and GRP78 and GPR94 ( Fig. 3A-F ), suggesting that ER stress was initiated by wogonoside treatment.…”
Section: Resultsmentioning
confidence: 88%
“…High concentrations of Ca 2+ can inhibit the synthesis of ATP by mitochondria. The lack of ATP would affect cell growth and even lead to apoptosis [ 34 ]. In addition, oxidative stress can also activate the cellular apoptosis induced by caspase-3 [ 35 ].…”
Section: Mt and Ovarian Functionsmentioning
confidence: 99%